Analysis of trade before and after the WTO: A case study of South Asia - Rana Ejaz Ali Khan; Muhammad Ijaz Latif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
Trade stimulates economic growth as well as create employment. The basic principles (of the WTO) make the system economically more efficient and cut the production and marketing costs. It gives consumers more choice, and a broader range of qualities to choose from. These are the basic benefits of world trading given by the WTO (WTO 2003). A number of studies have explained implications of the WTO with reference to developed and developing countries. How much trade has been increased by nations after the implementation of the WTO remained an ambiguous estimation. The increase in trade can result into benefits of the WTO. Generally, it is taken that developing economies have taken lesser tranche of the global trading. By applying the before-after approach we have tried to estimate that how much trade is increased in South Asian counties. How much the agriculture and industrial sectors were contributing in boosting the trade of the nations before the WTO and how it is doing after the WTO. It concluded that trade of the South Asian nations has not been increased up to the expectations that results in to low gaining of benefits from world trade.
Keywords: 330; Exports; Imports; International Trade; South Asia; WTO; Agriculture; Industry